Fast ion induced luminescence of silica implanted by molecular hydrogen - Kalantaryan, O.; Kononenko, S.; Zhurenko, V.; Zheltopyatova, N. (Functional Materials, 2014)
We studied silica implanted by 420 keV H⁺ and 210 keV H⁺ ions up to absorption doses 3.5⋅ 10²¹ particles per cm³ by ionoluminescence technique. We used some probe beams of molecular and atomic hydrogen ions for luminescence excitation from the implanted samples: 420 keV H⁺, 210 keV and 420 keV H⁺. It was found that significant changes in the spectrum shape of silica were observed at wavelength range of 550-650 nm during continuous ion irradiation. Using different probe beams we performed the comparative luminescence study of the silica samples implanted by H⁺ and H⁺ at the same absorption dose. For these samples we observed the difference in the spectra at wavelength range 610-650 nm, which corresponds to luminescence from non-bridge oxygen centers of silica. The possible explanation of the differences in the spectra shape was suggested.